The role of inventories for the propagation of aggregate fluctuations: Lessons for Bulgaria (1999-2019) - Aleksandar Vasilev (Journal of Economics and Administrative Sciences, 2021)
Purpose: Inventories are introduced as a productive input into a real-business-cycle (RBC) setup augmented with government. Design/Methodology/Approach: The model is calibrated to Bulgarian data for the period 1999-2019. The quantitative importance of the presence of inventories is investigated. Findings: The quantitative effect of inventories is found to be important: decreasing consumption volatility, and increasing employment variability. Those, results, however, are at the expense of decreasing wage volatility, and increasing investment volatility, and generally worsening the contemporaneous correlations of the main variables with output. Originality/Value: Fluctuations in inventory levels matter for business cycle fluctuations in Bulgaria, which is a novel result. Still, there is need for more research on the incorporation of inventories into RBC models to fit better Bulgarian experience.
Keywords: E32; E24; 330; business cycles; inventories; Bulgaria